Association of the interaction between interleukin-1β gene polymorphism and smoking status with the diabetic nephropathy risk in a Chinese Han population - Tianyue Xie; Zhuqi Tang (Diabetology & Metabolic Syndrome)
Abstract Objectives we aimed to evaluate the association of interleukin-1β (IL-1β) gene single nucleotide polymorphisms (SNPs) and its interaction with smoking status on diabetic nephropathy (DN) risk in a Chinese Han population. Methods The Hardy-Weinberg equilibrium (HWE) was tested by using SNPStats ( https://www.snpstats.net/start.htm ), which was also used for testing the relationship between four SNPs and DN risk and haplotype analysis. The SNP- SNP and gene- smoking interaction were verified by using generalized multifactor dimensionality reduction (GMDR) model. Results Logistic regression suggested that the DN risks of participants with rs16944- G allele were significantly higher than those with AA genotype, adjusted OR (95%CI) = 1.62 (1.24–2.01) for AG versus AA, 1.41 (0.75–2.12) for GG versus AA. Additionally, we also found that participants with rs3917356- T allele had an obviously higher DN risk than those with CC genotype, adjusted OR (95%CI) = 1.75 (1.34–2.19) for CT versus CC, 1.87 (1.23–2.54) for TT versus CC. GMDR model found a significant two-locus model (P = 0.011) including rs16944 and smoking. Compared with non- smokers with rs16944- AA genotype, smokers with rs1225404 AG or GG genotype had the highest DN risk after covariates adjustment, OR (95%CI) was 3.04 (1.98–4.12). We also found a haplotype containing rs1143634- T and rs3917356- T was associated with higher DN risk. Conclusions we found that the rs16944- G and rs3917356- T allele, interaction between rs16944 and smoking, haplotype containing rs1143634- T and rs3917356- T were all associated with increased DN risk.